Hyperglycemia in Acute Subarachnoid Hemorrhage (Medical Forum Monthly, 2020)
Objective: To determine the frequency of hyperglycemia in patients presented with subarachnoid hemorrhage.Study Design: Cross-sectional/observational studyPlace and Duration of Study: This study was conducted at the Department of Neurology, Sharif Medical City Hospital, Lahore from 1st August 2017 to 31st March 2020.Materials and Methods: One hundred and five patients of both genders with ages 20 to 75 years presented with subarachnoid hemorrhage were enrolled. Patient’s detailed demographics including age, sex, body mass index and Hunt Hess grade were recorded after taking informed consent. Serum glucose level was examined. Hyperglycemia was defined as serum glucose level >140mg/dl.Results: Seventy-six (72.38%) were males while 29 (27.62%) were females. Thirty-two (30.48%) patients were ages <40 years, 56 (53.33%) were ages 41 to 60 years and 17 (16.19%) were ages above 60 years. Hyperglycemia was found in 67 (63.81%) patients while 38 (36.19%) patients were non-hyperglycemic.Conclusion: The frequency of hyperglycemia in patients with subarachnoid hemorrhage was too high.